Efficacy and safety of endoscopic ultrasound-guided gastrojejunostomy in patients with malignant gastric outlet obstruction and ascites - Tala Mahmoud; Andrew C. Storm; Ryan J. Law; Veeravich Jaruvongvanich; Rabih Ghazi; Rami Abusaleh; Eric J. Vargas; Fateh Bazerbachi; Michael J. Levy; Mark J. Truty; Vinay Chandrasekhara; Barham K. Abu Dayyeh (Endoscopy International Open, 2022)
Background and study aims Endoscopic ultrasound-guided gastrojejunostomy (EUS-GJ) is an endoscopic procedure for treating gastric outlet obstruction (GOO). Limited data exist regarding the safety and efficacy of EUS-GJ in patients with malignant GOO with ascites. Thus, we aimed to study the outcomes and safety of EUS-GJ in GOO patients with vs. without ascites. Patients and methods This is a retrospective cohort study of patients with malignant GOO who underwent successful EUS-GJ at a tertiary care academic center. Primary outcomes included the efficacy and safety of EUS-GJ. Secondary outcomes included 30-day readmission, reintervention, and survival utilizing Kaplan-Meier analysis. Results A total of 55 patients (mean age of 67.0 ± 11.3 years, 40.0 % female) who underwent EUS-GJ, of whom 24 had ascites (small in 22, large in 2) were included. Clinical success was achieved in 91.7 % and 93.5 % (P = 1.00) of patients with and without ascites, respectively. A higher rate of adverse events (AEs) was noted in patients with ascites but this was not statistically significant (37.5 % vs. 19.4 %, P = 0.13). Four patients in the ascites group (16.6 %) developed clinical evidence of peritonitis or sepsis post-EUS-GJ. Eight patients with ascites developed worsening ascites within a month of EUS-GJ. In contrast, only one patient without ascites developed evidence of new ascites. The median survival of patients was not significantly different between the two groups (patients with ascites: 129 days vs. patients without ascites: 180 days, (P = 0.12). Conclusions The efficacy EUS-GJ in the presence of ascites is promising; however, the safety profile remains concerning given the high rate of AEs, specifically peritonitis and sepsis.